Hieracium sourekii (Asteraceae), a new species in the H. senescens aggregate and the discovery of H. subortum in the Sudetes, Poland - Szeląg, Zbigniew (Phytotaxa, 2025)
Hieracium sourekii is a new, triploid, apomictic species discovered in the Karkonosze Mountains (Giant Mountains) in the Sudetes, Poland. It combines the morphological features of H. alpinum and H. subortum, and belongs to the H. senescens aggregate. The epithet honours Josef Šourek, Czech botanist, an expert on the flora of the Karkonosze Mountains. Hieracium subortum is neotypified from specimens found in a new site in Poland as no original material has been traced. Hieracium sourekii and H. subortum are illustrated with photos of the type specimens and live plants.